4(2) - 3(1) = 5
Chat with our AI personalities
{-1,-2}
4x+3/3=y
You have 2 equations and 2 unknowns so you can solve 2x-3y = -11 y = 4x -3 2x - 3y = -11 -4x + y = -3 multiply 1st equation by 2 both sides: 4x-6y = -22 -4x + y = -3 add: -5y = -25 y = 5 substitute y = 5 into either equation: -4x+y = -3 -4x +5 = -3 -4x = -8 x = 2
Presumably this is a simultaneous equation in the form of: -4x+3y = 27 -2x+y = -1 Multiply all terms of the bottom equation by 2: -4x+3y = 27 -4x+2y = -2 Subtract the bottom equation from the top equation remembering that a - - is equal to a + Meaning that -4x - -4x = 0 and 27 - -2 = 29: So y will = 29 Substitute the value of y into the original equations to find the value of x Therefore: x = 15 and y = 29
4x + 3y = 1y = 2x + 8 Take the first part: 4x + 3y = 1y 4x = 1y - 3y 4x = -2y x = -y/2 Substitute x in second part: 1y = 2x + 8 1y = -2y/2 + 8 1y = -1y + 8 2y = 8 y = 4 Substitute y into either part: 1y = 2x + 8 1(4) = 2x + 8 4 - 8 = 2x -4 = 2x x = -2 Therefore: x = -2 y = 4